Nothing Special About Banks: Competition and Bank Lending in Britain, 1885–1925 - Braggion, Fabio; Dwarkasing, Narly; Moore, Lyndon (Review of Financial Studies, 2017)
We investigate the impact of increasing bank concentration on bank loan contracts in a lightly regulated environment that allows us to abstract from possible confounding effects of regulation and focus on the “pure” effects of competition on bank lending. We study over 30,000 British bank loans over the period 1885 to 1925. Borrowers in counties with high bank concentration received smaller loans and posted more collateral than borrowers in other counties. In high concentration counties, the quality of loan applicants improved, suggesting that banks restricted credit, not that the quality of loan applicants had worsened. Received February 4, 2016; editorial decision December 20, 2016 by Editor Philip Strahan.